Core strengthening dan breathing exercises sebagai intervensi antropometri pada perempuan obesitas - Hasanah, Uswatun; Juliani Saputri; Akhmad Ridhani; Utomo Wicaksono; Dadan Prayogo; Bernadus Sadu; Rizky Ridhayanti (Physical Education Departement of University PGRI Jombang, 2025)
Obesity is a global health issue associated with an increased risk of metabolic diseases such as diabetes mellitus, hypertension, and cardiovascular disorders. Women are more susceptible to abdominal obesity due to higher visceral fat accumulation. This study aimed to investigate the effect of a combined core strengthening and breathing exercise program on reducing body mass index (BMI) and waist circumference in obese women. A one-group pretest-posttest design was used, involving 15 obese female participants aged 20–35 years. The intervention was conducted over six weeks, with a frequency of three sessions per week. The exercise program included core strengthening exercises (pelvic tilt, supine marching, bridge, modified and full bird-dog, side leg lift, wall plank, single-leg bridge, modified and full side plank, light curl-up, dynamic bridge, modified full plank, light wall sit, flutter kick, and superman hold) and breathing exercises (diaphragmatic breathing and pursed-lip breathing). BMI and waist circumference were measured before and after the intervention. Paired sample t-test results showed a significant reduction in BMI from 27.63 ± 0.76 to 26.61 ± 0.76 (p < 0.001) and in waist circumference from 91.07 ± 3.57 cm to 86.73 ± 3.22 cm (p < 0.001). These findings suggest that the combined exercise program is effective in improving anthropometric indicators related to obesity. This non-pharmacological intervention may be recommended for obesity management in women. Further research is needed to assess its long-term effects and potential integration with other lifestyle interventions such as dietary changes and health education. Further research is needed to assess its long-term effects and potential integration with other lifestyle interventions such as dietary changes and health education.